Production of inhalation phage powders using spray freeze drying and spray drying techniques for treatment of respiratory infections - Leung, Sharon S.Y. (Pharm Res, 2016)
PURPOSE: The potential of aerosol phage therapy for treating lung infections has been demonstrated in animal models and clinical studies. This work compared the performance of two dry powder formation techniques, spray freeze drying (SFD) and spray drying (SD), in producing inhalable phage powders. METHOD: A Pseudomonas podoviridae phage, PEV2, was incorporated into multi-component formulation systems consisting of trehalose, mannitol and L-leucine (F1 = 60:20:20 and F2 = 40:40:20). The phage titer loss after the SFD and SD processes and in vitro aerosol performance of the produced powders were assessed. RESULTS: A significant titer loss (~ 2 log) was noted for droplet generation using an ultrasonic nozzle employed in the SFD method, but the conventional two-fluid nozzle used in the SD method was less destructive for the phage (~0.75 log loss). The phage were more vulnerable during the evaporative drying process (~0.75 log further loss) compared with the freeze drying step, which caused negligible phage loss. In vitro aerosol performance showed that the SFD powders (~80% phage recovery) provided better phage protection than the SD powders (~20% phage recovery) during the aerosolization process. Despite this, higher total lung doses were obtained for the SD formulations (SD-F1 = 13.1 ± 1.7 × 10(4) pfu and SD-F2 = 11.0 ± 1.4 × 10(4) pfu) than from their counterpart SFD formulations (SFD-F1 = 8.3 ± 1.8 × 10(4) pfu and SFD-F2 = 2.1 ± 0.3 × 10(4) pfu). CONCLUSION: Overall, the SD method caused less phage reduction during the powder formation process and the resulted powders achieved better aerosol performance for PEV2.